2011
DOI: 10.1007/s00431-011-1555-x
|View full text |Cite
|
Sign up to set email alerts
|

Acute rheumatic fever in the Central Anatolia Region of Turkey: a 30-year experience in a single center

Abstract: Although the incidence of ARF has decreased in the last decade, it still continues to be an important public health problem in Turkish pediatric population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
40
4
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(57 citation statements)
references
References 18 publications
10
40
4
3
Order By: Relevance
“…Between 2001-2012 years the incidence of acute rheumatic fever was detected as 2.3/100.000 throughout Turkey. In the same period, Örün et al (12) found the incidence of acute rheumatic fever as 21/100.000 in Central Anatolia region. Narin et al (22) reported the incidence as 7.4/100.000 between the years 1998-2011 in Kayseri.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Between 2001-2012 years the incidence of acute rheumatic fever was detected as 2.3/100.000 throughout Turkey. In the same period, Örün et al (12) found the incidence of acute rheumatic fever as 21/100.000 in Central Anatolia region. Narin et al (22) reported the incidence as 7.4/100.000 between the years 1998-2011 in Kayseri.…”
Section: Discussionmentioning
confidence: 89%
“…The actual incidence of population-based surveillance studies reach up to 500/100.000 (9,10). Until now, there is not any nationwide study performed to detect the incidence and prevalence of acute rheumatic fever in Turkey, instead the studies were performed regionally (11,12). The aim of this study is to determine the incidence of acute rheumatic fever throughout Turkey.…”
Section: Introductionmentioning
confidence: 99%
“…Little information is available on the current incidence of RF in Turkey; however, it appears to be moderate (in at least two localities, Table ). Its effects are profound: In 2004, RHD was the fourth leading cause of death in 15‐ to 59‐year‐olds .…”
Section: Resultsmentioning
confidence: 99%
“…Her ne kadar Avrupa ve Amerika Birleşik Devletleri'nde ARA insidansı 1/100.000 oranla ender olsa da gelişmekte olan ülkelerde 50/100.000'e kadar yükselebilen oranlarla hâlâ kardiyovasküler mortalite ve morbiditenin başlıca nedenlerindendir (3) . Türkiye geneli için ARA insidansını yansıtan yeterince veri olmasa da Ankara'da 1980 ve 2009 yılları arasındaki ARA hastalarının değerlendirildiği bir çalışmada, insidans 1980-1989 yılları arasında 37/100.000, 1990-1999 yılları arasında 60/100.000 ve 2000-2009 yılları arasında 21/100.000 olarak hesaplanmıştır (32) . Negatif hızlı antijen test sonuçlarının kültürle doğrulan-ması, yanlış tanı ve eksik tedavinin önlenmesi, böylece ARA gibi önemli komplikasyonların engellenmesi açısından oldukça kritiktir.…”
Section: Discussionunclassified